Billroth II with Braun Enteroenterostomy Is a Good Alternative Reconstruction to Roux-en-Y Gastrojejunostomy in Laparoscopic Distal Gastrectomy - Long-Hai Cui; Sang-Yong Son; Ho-Jung Shin; Cheulsu Byun; Hoon Hur; Sang-Uk Han; Yong Kwan Cho (Gastroenterology Research and Practice, 2017)
Background. Although Billroth II (BII) reconstruction is simpler and faster than Billroth I or Roux-en-Y (RY) reconstruction in patients undergoing totally laparoscopic distal gastrectomy (TLDG), BII reconstruction is associated with several complications, including more severe bile reflux. BII Braun anastomosis may be a better alternative to RY reconstruction. Methods. This retrospective study included 56 consecutive patients who underwent TLDG for gastric cancer, followed by BII Braun or RY reconstruction, between January 2013 and December 2015. Surgical outcomes, including length of operation, quantity of blood lost, and postoperative complications, were compared in the two groups. Results. Clinicopathological characteristics did not differ between the BII Braun and RY groups. Mean length of operation was significantly longer in the RY than the BII Braun group (157.3 min versus 134.6 min, p < 0.010), but length of hospital stay, blood loss, and complication rate did not differ between the two groups. Ileus occurred in three patients (10.0%) in the RY group. Endoscopic findings 6 months after surgery showed bile reflux in seven (28%) patients in the BII Braun group and five (17.2%) in the RY group (p = 0.343), but no significant differences in rate of gastric residue or degree of gastritis in the remnant stomach in the two groups. Conclusions. B-II Braun anastomosis is a good alternative to RY reconstruction, reducing length of operation and ileus after TLDG.